O destombamento do Pico de Itabirito: paisagem, patrimônio e mineração - Thaís Lanna Junqueira (2019)
The process of classifying and later removal of Pico de Itabirito (MG) from the national heritage list, occurred in the 1960s, is the object of this dissertation. The research aimed to investigate and explain the process, from the perspective of cultural heritage as a discursive construction, made of conflicts of values, powers and interests. It was sought to understand, through extensive documentary research, the discourses that based the action of the agents involved in the process and the impact that the episode had on the population, relating these elements to the historical context in which they were inserted. Here we present, therefore, the history of the symbolic construction of the Peak as a remarkable landscape, the trajectory of mining in Itabirito and the patrimonialization of natural assets by Dphan, as well as relevant aspects of Decree-Law No. 3.866, of 1941, which establishes the cancellation of classification in the national heritage list. The research has shown that cultural heritage, as discursive elaboration, is conditioned by the fluctuating conflicts of power that occur in the various political contexts. This makes its supposed sacredness coexist with a dimension of fragility, making the preservation and destruction of heritage properties two sides of the same coin.